Adenovirus infection as possible cause of acute liver failure in a healthy child: A case report - Ferda ÖZBAY HOŞNUT; Oğuz CANAN; Figen ÖZÇAY; Banu BİLEZİKÇİ (Turkish Journal of Gastroenterology, 2019)
-